Pengaruh Keteladanan Guru PAK terhadap Karakter Kristiani dan Minat Belajar PAK Siswa/Siswi Kelas XI SMA Swasta HKBP 1 Tarutung Tahun Ajaran 2023/2024 - Nunut Hutabarat; Hisardo Sitorus; Andar Gunawan Pasaribu; Iwan Setiawan Tarigan; Arif Surpi Sitompul (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
This study aims to determine the effect of exemplary Christian Religious Education (PAK) teachers on Christian character building and learning interest of grade XI students of HKBP 1 Tarutung Private High School in the 2023/2024 school year. The research method used is descriptive quantitative with inferential statistics. The study population included all grade XI students, totaling 214 people, with a sample of 43 students (20% of the population). Data were obtained through a closed questionnaire totaling 55 items. The results of the analysis show: 1) There is a significant influence of exemplary PAK teachers on the formation of students' Christian character, with the value of F count 10.628> F table 4.08 and an influence of 20.6%; 2) The exemplary of PAK teachers also affects students' interest in learning, with the value of F count 24.274 > F table 4.08 and an influence of 37.2%; 3) The exemplary of PAK teachers has a simultaneous influence on the formation of Christian character and student interest in learning, with the value of F count 14.411 > F table 3.08 and an influence of 41.9%. This result shows that the exemplary role of PAK teachers plays an important role in the formation of Christian character and increasing students' interest in learning. Thus, Ha is accepted and H0 is rejected, which confirms that the teacher's example has a significant positive impact on students.